2019
DOI: 10.1016/j.biocon.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Research priorities for freshwater mussel conservation assessment

Abstract: Freshwater mussels are declining globally, and effective conservation requires prioritizing research and actions to identify and mitigate threats impacting mussel species. Conservation priorities vary widely, ranging from preventing imminent extinction to maintaining abundant populations. Here, we develop a portfolio of priority research topics for freshwater mussel conservation assessment. To address these topics, we group research priorities into two categories: intrinsic or extrinsic factors. Intrinsic fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
121
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 179 publications
(135 citation statements)
references
References 139 publications
1
121
0
1
Order By: Relevance
“…Despite all of this, freshwater mussels are globally threatened and many populations are in pronounced decline (Strayer et al, 2004;Graf and Cummings, 2007;Lopes-Lima et al, 2014b, 2018. Recent efforts have been implemented to better understand and conserve this group (Lopes-Lima et al, 2014a, 2014b, 2018, but there is still much to be done (see Ferreira-Rodríguez et al, 2019). Freshwater mussels are considered "permanent refugial organisms" , meaning they have limited dispersal abilities even under flow conditions, and are restricted to areas where water availability is permanent across many years.…”
Section: Introductionmentioning
confidence: 99%
“…Despite all of this, freshwater mussels are globally threatened and many populations are in pronounced decline (Strayer et al, 2004;Graf and Cummings, 2007;Lopes-Lima et al, 2014b, 2018. Recent efforts have been implemented to better understand and conserve this group (Lopes-Lima et al, 2014a, 2014b, 2018, but there is still much to be done (see Ferreira-Rodríguez et al, 2019). Freshwater mussels are considered "permanent refugial organisms" , meaning they have limited dispersal abilities even under flow conditions, and are restricted to areas where water availability is permanent across many years.…”
Section: Introductionmentioning
confidence: 99%
“…Such actions include the restoration of river dynamics and hydromorphology, an increase of floodplain habitats, improving water quality, and assisting the recovery of microhabitats by ensuring well-oxygenated substrates and a decrease of suspended solids (Dudgeon et al, 2006;Strayer et al, 2019). Remedial actions should remove the likely cause(s) for species decline (Bolland et al, 2010), so the management of fish host populations should also be included as a key management action in order to restore the reproductive potential of freshwater mussels in their natural habitats (Ferreira-Rodríguez et al, 2019).…”
Section: Conservation Importancementioning
confidence: 99%
“…from increased fine sediment deposition, excessive nutrient input, heavy metal accumulation, herbicides and fungicides used in agriculture), overexploitation (including exploitation of fish hosts), introduction of invasive alien species (IAS), and climate change (for a review see Lopes-Lima et al, 2017). Despite their threatened conservation status there is still a noticeable scarcity of information on their complex biology (Geist, 2010(Geist, , 2011Geist & Auerswald, 2007;Howard & Coffey, 2006;Lopes-Lima et al, 2014), particularly on their reproductive biology and on the fish-mussel relationship (Modesto et al, 2018), which may impair the implementation of effective conservation efforts (Ferreira-Rodríguez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that one of the most important problems for mussel conservation is recruitment cessation. Mussel populations without recently born juveniles will become extinct in the near future, even though the current size of the populations might be relatively large (Ferreira‐Rodríguez et al, ; Geist, ; Österling, Greenberg, & Arvidsson, ). Thus, long‐term monitoring targeting a wide age class of mussels is required.…”
Section: Introductionmentioning
confidence: 99%